Structural basis of the neuronal M-current by an asymmetric KCNQ2/3 channel assembly - Cheng, Xinyu; Wan, Shuangyan; Jiang, Dexiang; Zhang, Hangyu; Hu, Bin; Che, Tong; Nan, Weiwei; Zhou, Zhuo; Xiao, Chenxin; Zhong, Ling; Zhang, Yuting; Yu, Bo; et al. (浪淘沙预印本平台, 2025)
The heteromeric KCNQ2/3 channel constitutes the molecular correlate of the neuronal M-current, a potassium conductance essential for stabilizing resting membrane potential and controlling neuronal excitability. Despite its physiological and therapeutic importance, the structural basis for its unique functional properties—distinct from homomeric KCNQ2 or KCNQ3—has remained enigmatic, and its definitive subunit stoichiometry has been a subject of long-standing debate. Here, leveraging a fusion protein strategy and multiple stoichiometry-sensitive pharmacological tools, we determined cryo-electron microscopy structures of the human KCNQ2/3 channel in both apo and drug-bound states, which unveil an asymmetric assembly with a predominant 1:3 (KCNQ2:KCNQ3) stoichiometry. This architectural principle underlies the M-channel’s unique gating and pharmacology. Structural and functional analyses reveal that a reconfigured voltage-sensing domain and a pre-positioned C-terminal domain collectively lower the energy barrier for left-shifted voltage-dependent activation and enhanced PIP2 sensitivity. Furthermore, we elucidate the binding mechanism of the next-generation anticonvulsant XEN1101, demonstrating that its high selectivity for KCNQ2/3 arises from an optimized complementarity to the KCNQ3-dominated binding pocket within the heteromer. Our work resolves fundamental questions regarding the native architecture of the neuronal M-channel and establishes a structural foundation for the rational design of targeted therapies for epilepsy and related neurological disorders.